A review of the genus Drymeia Meigen, 1826 (Diptera: Muscidae) in Russia - Sorokina, Vera S.; Pont, Adrian C. (Zootaxa, 2015)
A key is provided to the 26 species of the genus Drymeia Meigen, 1826 known from Russia and four additional species that may be found in Russia (D. brumalis (Rondani, 1866), D. cantabrigensis (Huckett, 1965), D. gymnophthalma (Hennig, 1963), D. similis (Malloch, 1918)). The key includes the 10 new species here described from the mountains of South Siberia (D. acrostichalis sp. nov., D. aristata sp. nov., D. cilitarsis sp. nov., D. glabra sp. nov., D. grandis sp. nov., D. grisea sp. nov., D. longiseta sp. nov., D. phaonina sp. nov., D. puchokana sp. nov., D. triseta sp. nov.,) and other two new species from the Russian Arctic (D. cristata sp. nov., D. taymirensis sp. nov.). Five species (D. fasciculata (Stein, 1916), D. firthiana (Huckett, 1965), D. groenlandica (Lundbeck, 1901), D. quadrisetosa (Malloch, 1919), D. neoborealis (Snyder, 1949)) are newly recorded from Russia. Three new synonymies are proposed: D. pribilofensis (Malloch, 1921) (syn: D. inaequalis (Malloch, 1922)), D. setibasis (Huckett, 1965) (syn: D. gymnophthalma sibirica (Lavčiev, 1971, unavailable junior secondary homonym) and D. quadrisetosa (Malloch, 1919) (syn: D. amurensis (Lavčiev, 1971)). The male terminalia and the female ovipositors of the new species are illustrated. New faunistic data are given for some previously described species of Russian Drymeia.